2016
DOI: 10.1097/aog.0000000000001472
|View full text |Cite
|
Sign up to set email alerts
|

Phenazopyridine for Evaluation of Ureteral Patency

Abstract: ClinicalTrials.gov, https://clinicaltrials.gov/, NCT02424149.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Other adverse effects include somnolence (20%), dizziness (8%), ataxia (13%), and fatigue (11%). Phenazopyridine (pyridium) 200 mg is a relatively low−risk intervention that can be given preoperatively as a urogesic and has been shown to increase voiding trial success rates [94]. Table 4 formulates a multimodal medication bundle for MIGS on the basis of these data.…”
Section: Multimodal Opioid-sparing Analgesiamentioning
confidence: 99%
“…Other adverse effects include somnolence (20%), dizziness (8%), ataxia (13%), and fatigue (11%). Phenazopyridine (pyridium) 200 mg is a relatively low−risk intervention that can be given preoperatively as a urogesic and has been shown to increase voiding trial success rates [94]. Table 4 formulates a multimodal medication bundle for MIGS on the basis of these data.…”
Section: Multimodal Opioid-sparing Analgesiamentioning
confidence: 99%
“…The use of opioids and tricyclic antidepressants in patients undergoing a hysterectomy was found to be associated with POUR 63 . Three RCTs in patients that had POP or SUI surgery showed no differences in using phenazopyridine to decrease the incidence of POUR 24,66,67 …”
Section: Discussionmentioning
confidence: 99%
“…RCTs have demonstrated that the use of phenazopyridine does not decrease the risk of POUR in patients having MUS or pelvic organ prolapse surgical procedures. 24,66,67 87.50…”
Section: Q17 Does the Use Of Analgesics During Surgery Increase The I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Race was dichotomized into White or non-White for our analysis. Factors that could potentially affect voiding dysfunction (Charlson Comorbidity Index, operative time, and preoperative phenazopyridine administration) were also included as covariates in our model 9 . Charlson Comorbidity Index scores were split into mild risk (scores of 0–2) versus moderate/severe risk (scores of 3 or greater) categories for the regression analysis.…”
Section: Methodsmentioning
confidence: 99%